Concepções de professores sobre a resolução de problemas - Guimarães, Joice Silva Mundim (2019)
The research seeks to identify, analyze and discuss the conceptions of teachers who teach Mathematics about their work with content in the early years of elementary school, outlining a teaching proposal in light of the theoretical and scientific perspectives of Problem Solving that access teaching-learning-development of students. The thesis presents teachers who teach mathematics and their conceptions about Problem Solving - PR, the historical and theoretical perspective of PR, the field research of teachers' conceptions and a theoretical proposal to approach PR from the contributions of davydoviana theory. The methodological approach was the qualitative research, with the unfolding of the theoretical research, along with the questionnaire and interview instruments to perform the fieldwork. Thus, teachers' conceptions, identified in the data collection, led us to analyze and reflect on how the methodological approach of mathematics has been conducted, leading us to delineate a different didactic organization in the work with mathematical contents. For this, we use Davydov's theory, which proposes a process of teaching-learning-development of mathematical contents, based on the ascension movement from the abstract to the concrete that marks the construction of the student's theoretical thinking. The PR, in Davydov's perspective, is addressed in the student's study activity, which from the difficulties proposed by the teacher, the student gets involved with solving problems in the development of the study task. The course of the research evidenced the mismatch between the thought in the scientific world and the one carried out in the school context. Educational theories, focused on the teaching of mathematical content and PR, outline validated scientific proposals for the development of the subject, but these structures differ from the current context. We clarify that PR, before any action, is concerned with the trajectory of how the problem is solved, since this line resorts to scientific contents and fundamentals, which really matters for the education of students.